Innovative model for older inpatients falls predictors assessment: a prognostic cohort study - Lea Godino; Daniela Mosci; Elisa Ambrosi; Luisa Sist; Roberta Decaro; Paolo Chiari; Domenica Gazineo (Dissertation Nursing, 2025)
Background. In-hospital falls are avoidable accidents, but continue to be a high prevalent and incident patient safety issue. The 60% of falls are caused by more than one factor. An early identification and assessment of inpatients' high risk of falling, at the beginning of hospitalization, is unclear.